Properties of triticale protein films and their relation to plasticizing-antiplasticizing effects of glycerol and sorbitol - Aguirre, Alicia del Valle (2013)
Triticale protein films were prepared and the influence of glycerol and sorbitol on their functional properties was investigated. At equal plasticizer concentration glycerol-plasticized triticale films had higher moisture content at a given relative humidity than did sorbitol films. Films plasticized with sorbitol exhibited higher solubility than glycerol-plasticized films. Mechanical properties of films are strongly affected by relative humidity and considerably varied with the type and concentration of plasticizer used. Glycerol exhibited better plasticizing effect for triticale films. Tensile strength, Young's modulus and puncture force of the films decreased as the glycerol content increased. The increase in the tensile strength and Young's modulus of the films containing low levels of sorbitol was ascribed to the antiplasticization of the films. Films prepared with sorbitol had lower water vapor permeability values but tended to be stiff and in some cases too brittle for tensile measurements. Sorbitol plasticization of the triticale protein films approached saturation at the plasticizer level of 50%. This work contributes to the understanding of the plasticizing-antiplasticizing effects of glycerol and sorbitol on properties of protein films and may be useful in the handling of these films as new food packaging systems, in accordance with the specific requirements of potential users. © 2013.